2006
DOI: 10.1523/jneurosci.3388-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pain, Both Neuropathic and Inflammatory, Is Related to Frequency of Spontaneous Firing in Intact C-Fiber Nociceptors

Abstract: Spontaneous pain, a poorly understood aspect of human neuropathic pain, is indicated in animals by spontaneous foot lifting (SFL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
401
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(457 citation statements)
references
References 43 publications
31
401
3
3
Order By: Relevance
“…For our first model, we used intraplantar injection of CFA, which consists of a mixture of paraffin oil (85% vol/vol), mannide monooleate (15% vol/vol), and heatkilled Mycobacteria tuberculosis (1 mg/mL), and is an immunological adjuvant (13)(14)(15). Second, we chose a modified plantar incision (injury to the skin and underlying muscle) to model sterile tissue injury-based inflammation (16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…For our first model, we used intraplantar injection of CFA, which consists of a mixture of paraffin oil (85% vol/vol), mannide monooleate (15% vol/vol), and heatkilled Mycobacteria tuberculosis (1 mg/mL), and is an immunological adjuvant (13)(14)(15). Second, we chose a modified plantar incision (injury to the skin and underlying muscle) to model sterile tissue injury-based inflammation (16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…Following the CFA injection, thermal hyperalgesia and mechanical allodynia were analyzed with Hargreaves and von Frey tests, respectively, at days 1, 2, 3, 4, and 10. The spontaneous pain assessment was performed in a modified version (Djouhri et al, 2006). Briefly, 20 l of CFA was injected into the side of the right knee and the plantar surface of the right paw.…”
Section: Methodsmentioning
confidence: 99%
“…Ectopic discharge in sensory fibers in models of peripheral neuropathy has been proposed in a number of models (Djouhri et al, 2006;Han et al, 2000;Liu et al, 2000c). Several studies have reported that systemic administration of lidocaine decreases ectopic activity recorded from injured peripheral sensory fibers (Chabal et al, 1989;Devor et al,1992;Omana-Zapata et al,1997a;Sotgiu et al, 1992) and reduces neuropathic pain (Brochu et al, 2006;Erichsen et al, 2003;Sinnott et al, 1999;Smith et al, 2002).…”
Section: Contribution Of Peripheral Drive To Spontaneous Activity Of mentioning
confidence: 99%